Economic Feasibility and Risk Assessment of Purse Seine Fishery Production Based on Fleet Capacity in Ohoi Sathean, Southeast Maluku Regency (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study analyzes the economic feasibility and assesses the production risk of the purse seine business based on the fleet capacity in Ohoi Sathean. The types of data needed are primary and secondary data collected using data triangulation. The number of samples is 14 fleets with capacities of 10 GT, 26 GT, 27 GT, and 30 GT. Data were analyzed using business feasibility analysis and business sensitivity analysis. The results of the business feasibility analysis showed that the highest value of RC ratio = 2.13 for a fleet of 10 GT means better operational efficiency, the highest investment criterion value NPV = USD 483,570, BC ratio = 6.39, PP = 2.55, and IRR = 98% for a fleet of 27 GT means better investment feasibility. The sensitivity of the purse seine business to the condition of fuel increase for kerosene 27% and diesel 30%, the highest value of RC ratio = 2.05 for the 10 GT fleet, the highest investment criterion value NPV = USD 205,791, BC ratio = 3.29, IRR = 51% for the 27 GT fleet, while PP = 4.76 years for the 10 GT fleet. In the condition of a 20% decrease in production, the highest value RC ratio = 1.97 is in the 10 GT fleet, the highest investment criteria in NPV = USD146,864, BC ratio = 2.68, and IRR = 41% in the 27 GT fleet, while PP = 5.80 is the lowest in the 10 GT fleet. The 10 GT purse seine business is efficient against changes in inputs and outputs, and the 27 GT is suitable for changes in inputs and outputs. The study aims to increase the efficiency and effectiveness of 26 GT and 30 GT fleets, and support the development of 10 GT and 27 GT purse seine to optimize catches.